Internalisasi Program Pengembangan Bakat Minat di TPQ Masjid Agung Baitussalam Purwokerto - Bambang Purwadi, Najwah Addina; Wahyuningtyas, Anti; Lestari, Bunga Citra; Maolana, Firda Nur Alif (Jumat Pendidikan: Jurnal Pengabdian Masyarakat, 2025)
Education is not only a role of transferring knowledge, but also aims to make students feel experiencing something that makes them understand the essence of themselves, and internalize the values contained in their experience as an ideal concept that will be applied in their lives. The purpose of developing interests and talents is to optimize individual development in areas of interest. The Al-Qur'an Education School (TPQ) is a non-formal educational institution that is not only limited to teaching how to read the Al-Qur'an correctly, but also a place for students to develop their potential. The research was conducted at TPQ Ta'limul Qur'an lil Aulad which is located at the Great Mosque of Baitussalam Purwokerto. The method used is the field research method, which is research whose object is about certain conditions in an area in a community group. The research is included in descriptive qualitative research. Data collection uses observation, interview, and documentation methods. This research uses the Participatory Action Research (PAR) method by being directly involved in teaching and learning activities at TPQ. Providing guidance programs for developing talents and interests with the right methods, tailored to the problems that exist in students. As well as coaching for educators is carried out by assisting teaching and learning activities so that learning is more varied and able to improve the reading of students properly.